Energy-Efficient Routing Path Selection Using CTSP and M-CTSP Protocols in Underwater Wireless Sensor Networks (UWSNs) - Khan, Abdul Moid (UMA Editorial, 2025)
Underwater Wireless Sensor Networks (UWSNs) have become essential for various underwater applications such as oceanographic data collection, environmental monitoring, underwater exploration, and military surveillance. However, designing efficient and energy-aware communication protocols in the challenging underwater environment is a significant challenge. Factors like limited battery replacement options, dynamic topologies caused by node mobility (due to water currents), high propagation delays, and restricted bandwidth require innovative solutions for data routing to extend network lifespan and enhance communication reliability. This thesis makes a significant contribution to the field of UWSN communication by introducing two robust, energy-efficient routing protocols tailored for static and mobile underwater environments: the Clustering-Traveling Salesman Protocol (CTSP) and the Mobile-Clustering Traveling Salesman Protocol (M-CTSP). These protocols employ clustering techniques and optimization methods based on solving the Traveling Salesman Problem (TSP) to improve energy efficiency and reliability of data transmission in both static and dynamic underwater settings. In the CTSP protocol, we consider a static UWSN scenario where sensor nodes are organized into clusters. We select cluster heads (CHs) based on optimal positioning, and member nodes send their data to CHs for aggregation. To determine the shortest possible path for a mobile sink or data collector to visit all CHs in a tour, we use the TSP algorithm. This approach helps reduce overall communication energy costs and transmission delays. CTSP places emphasis on minimizing long-distance communication by relying on localized transmissions, resulting in substantial reduction of energy consumption compared to traditional routing protocols like LEACH. Building upon CTSP, we propose M-CTSP protocol which accommodates mobility of sensor nodes¿a common characteristic in real underwater environments.

In M-CTSP, all nodes experience slight shifts in their locations due to water currents. The protocol adapts by dynamically reselecting cluster heads based on residual energy levels and proximity to cluster centroids. Each round requires recalculation of mobile sink path using TSP optimization ensuring routing paths remain energy-efficient despite constantly changing network topology. This adaptive strategy effectively addresses the challenges posed by dynamic node locations, resulting in improved packet delivery rates, balanced energy consumption, and longer network lifetimes. Comprehensive simulations and performance evaluations demonstrate that both CTSP and M-CTSP significantly outperform traditional routing protocols in UWSNs. CTSP reduces overall energy consumption by up to 50%, while M-CTSP achieves up to 40% energy savings, a 15% improvement in packet delivery ratio, and a 30% increase in network lifetime compared to LEACH and EECBP-FOA. The results affirm the feasibility and efficiency of using clustering combined with TSP-based optimization to tackle the critical issues of energy conservation and reliable communication in UWSNs.
Keywords: Acústica submarina - Tesis doctorales; Ingeniería oceanográfica; Consumo de energía; Clustering; Data routing; Energy efficiency; Traveling salesman problem; Underwater sensor networks